Characterisation of primary copper ore for block caving at the El Teniente mine, Chile - Brzovic, Andres (Curtin University, 2010)
This thesis investigated the rock mass geotechnical behaviour of primary copper ore at the El Teniente mine in Chile, which has been described as a massive and competent rock mass. The rock mass was characterised considering different structural data collection techniques and mapping scales. Modifications were made to the traditional sampling methodologies to better determine the observed geological discontinuities within primary copper ore. It was found that few open geological discontinuities, mainly the widely spaced large scale sub-vertical faults, are observed within primary ore, and this could be in agreement with the observed “competent” and “massive” rock mass behaviour at the mine site. The study also found a high frequency of small scale stockwork veins (cemented joints), which define at least three semi-orthogonal set orientations mine wide.The faces of caved rock blocks found in the production level draw points were also characterised and an empirical criterion to define weak discontinuities that define caved blocks was established. From these observations, it can be concluded that the geological discontinuities (veins) having less than 1/3 of hard minerals as infill (hard mineral means Mohs scale of hardness ≥ 4) and thickness greater than or equal to 2mm may also be the weaker path where a competent rock mass fail under caveinduced stress conditions. This empirical definition was applied for the structural data collected from different geological units and mine sectors of the El Teniente mine. The results allowed a differentiation of several geotechnical units where traditional rock mass classifications schemes failed.The observed rock mass behaviour during caving operations was back analysed to correlate with the new geotechnical units defined using that empirical definition. The back analysis studies included the rock damage as mine overbrake in mine drive at the undercut level, fragmentation performance, and mine seismicity recorded within a rock volume completely caved. A mine scale finite element numerical model was also built to assess the stress state around excavations during caving propagation. Damage orientation determination by seismic focal solutions was used to correlate against collected structural data to investigate the influence of weak discontinuities during block caving performance.